Conflict and reconciliation : looking back into Malaysian history / Qasim Ahmad - Ahmad, Qasim (Universiti Teknologi MARA, Shah Alam, 2008)
Compared to internal or domestic conflicts that have taken place in many other countries, those that have occurred in Malaysia/Malaya have been relatively more confined, the violence and the bloodshed involved notwithstanding. Nevertheless the impact that those conflicts has had on the nation’s history and body politics is by no means insignificant. That be the case, the manner in which those conflicts has been resolved, or the ways reconciliations were arrived at are equally significant, or, arguably, even more so.